Management of bean anthracnose through chemicals - S.K. SUGHA2, P.N. SHARMA1 and (Indian Phytopathology, 2002)
Field trials on the management of anthracnose (Colletotrichum lindemuthianum) of Phaseolus vulgaris with fungicides were conducted during 1990-91 and 1991-92 in Kinnaur, Himachal Pradesh, India. Seed treatment with thiram 75 WP, carbendazim 50 WP, carbendazim + thiram, mancozeb 75 WP, triadimenol 15 DS and metsulfovax 20 WP at 2.5 g/kg seed gave good control of seedborne infection, with carbendazim and carbendazim + thiram being the most effective treatments. Seed treatment followed by 2 or 3 foliar sprays of mancozeb (0.25%) 45, 60 and 75 d after sowing effectively managed the disease resulting in increased yields.